Transição da Educação Infantil para o Ensino Fundamental: contribuições da Teoria Histórico-Cultural pelo olhar dos professores - Machado, Rosa Cleide Marques (2022)
This research, based on historical-cultural theory, aimed to investigate the multiple determinations in the transition from Early Childhood Education to Elementary School, which constitutes one of the elements interfering in the failure rate at the beginning of elementary school. To understand this passage, it is discussed the conception of guiding activities and it is investigated how it is understood by the teacher of the 1st. fundamental year. Besides, it was analyzed the publications about that subject, in the BDTD - Library of Theses and Dissertations and in SciELO - Scientific Electronic Library Online, from 2010 to 2020. With semi-structured scripts, 26 (twenty-six) teachers who work in the 1st year of 15(fifteen) elementary schools in the municipality of Cascavel (PR), were interviewed. Those school correspond to the two largest and the two smallest ones in each geographic region of the municipality surveyed. The school’s selection was based on the student’s number. In the process of analyzing the collected data, the following categories emerged: the concepts of Guide Activity, Play of social roles and Study Activity - that drive the child's development in this passage from the perspective of the Historical-Cultural Theory, which underlies the curriculum of the municipal network of Cascavel -; and the difficulties and possibilities of overcoming the transition between Early Childhood Education and Elementary School. The results reveal that this transition is a peculiar moment in the schooling process, in which the new conditions involving the child require faster transformations in their development, placing the teacher in front of new pedagogical challenges determined by factors related to the child, to the teacher, to the family and to public policies. Although there is a dialectical articulation between these factors, the data highlight the importance of the teacher and the public policies that regulate their working conditions, to conduct this transition, which is complex and multi-determined. This process requires that initial and continuing teacher formation, prepare him for a pedagogical praxis that places him, as well as the students, in Study Activity, whose motive turns to humanization, that is, to the development of theoretical-critical thinking through the appropriation of scientific knowledge historically developed by men. Thus, it will be contributing to a social insertion that can promote a transformation, in the sense of equalizing access to education, health and adequate living conditions.